2017
DOI: 10.31227/osf.io/tkzcj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Growth and Yield Responses of Three Sweet Corn (Zea mays L. var. Saccharata) Varieties to Local-based Liquid Organic Fertilizer

Abstract: Abstract-Solid organic fertilizing for organically sweet corn production should be combined with foliar application to improve fertilizing effectiveness. Each sweet corn variety had different response to particular liquid organic fertilizer (LOF). This experiment aimed to determine growth and yields of three sweet corn varieties to local-based LOF was conducted at CAPS research station (950 m above sea level) from March to June 2015, arranged in a factorial completely randomized block design with three replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
1
11
0
4
Order By: Relevance
“…The use of a single green biomass for liquid organic fertilizer might provide high particular nutrient content, but low in other nutrients. This was confirmed by our previous result [12], [13], [14] where tithonia-enriched liquid organic fertilizer contained 3,36% N, 146 ppm P, and 0.033% K. Although nitrogen content of this liquid organic fertilizer somehow comply with the standard quality for organic fertilizer issued by Indonesian Standardization Board (SNI 19-7030-2004) where total N should be > 0.4 %, but P and K content were very much lower than standard (SNI-19-7030-2004) which must be above 0.10% (P 2 O 5 ) and 0.20% (K 2 O), respectively.…”
Section: J C/nsupporting
confidence: 90%
See 2 more Smart Citations
“…The use of a single green biomass for liquid organic fertilizer might provide high particular nutrient content, but low in other nutrients. This was confirmed by our previous result [12], [13], [14] where tithonia-enriched liquid organic fertilizer contained 3,36% N, 146 ppm P, and 0.033% K. Although nitrogen content of this liquid organic fertilizer somehow comply with the standard quality for organic fertilizer issued by Indonesian Standardization Board (SNI 19-7030-2004) where total N should be > 0.4 %, but P and K content were very much lower than standard (SNI-19-7030-2004) which must be above 0.10% (P 2 O 5 ) and 0.20% (K 2 O), respectively.…”
Section: J C/nsupporting
confidence: 90%
“…The source of green biomass should be a combination of several green biomasses in order to produce liquid organic fertilizer with high N, P, K, Ca, and Mg content. In addition, it also important to mixture the green biomasses with other natural composting material, such as poor soil [36], wood ash [37], cow manure [12], [13], [14], [38] in order to increase composting rates, nutrient quality and crop yields. The use of a single green biomass for liquid organic fertilizer might provide high particular nutrient content, but low in other nutrients.…”
Section: J C/nmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also indicated that liquid organic fertilizer significantly provided better growth and yield of sweet corn [24], [18], [25]. However, [26] concluded that growth and yield of sweet corn were not affected by local based liquid organic fertilizer. Application of liquid organic fertilizer has been confirmed to increase sweet corn uptake of nitrogen but phosphorus and potassium.…”
Section: Introductionmentioning
confidence: 95%
“…Organic farming takes benefit for its nutrient availability mainly from organic fertilizers. Organic fertilization is reported to improve soil quality and increases crop performance [1]- [5]. Along with the release of plant nutrients, application of such fertilizer often also carries a lot of weed seed species.…”
Section: Introductionmentioning
confidence: 99%